A comparative analysis of technical proficiencies: Viktor Axelsen Versus Anders Antonsen in Men’s Singles Badminton during the 2023 world tour / Muhammad Nabil Esa ... [et al.]. - Esa, Muhammad Nabil; Ismail, Arisya; Abdul Harith, Anis Shafira; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Mud Puad, Sharifah Maimunah Syed; Saiful Annur, Muhamad Safiq (2024)
This study conducts a comparative analysis of technical characteristics between top world-ranking and Top 1 Malaysia Athletes in men’s singles badminton matches during the 2023 World Tour. The objective of this research is to analyse gameplay between two players, providing insights for coaches and athletes to enhance their training and performance techniques. The focus of this study is Viktor Axelsen, the top 1 world ranking, and Lee Zii Jia, the Malaysian athlete. The technical characteristics that have frequently been analysed were (serve, drop, net, smash, lob, defence, drive and clear). Variables were obtained using YouTube videos and notational analysis r = 0.99 and % of error 0.3%. Mann-Whitney U was used to describe and to determine the difference in the technical characteristics used by the Top 1 World Ranking and Top 1 Malaysia Athletes, between the groups’ analyses, significant found out only seven out of 16 (success and unsuccess) which was lob unsuccess (p = 0.03, r = 0.252), clear success (p = 0.001, r = 0.60), clear unsuccess (p = 0.021, r = 0.28), drive unsuccess (p = 0.001, r = 0.46), defend unsuccess (p = 0.001, r = 0.51), drop unsuccess (p = 0.35, r = 0.23) and smash unsuccess (p = 0.016, r = 0.29). The study revealed that technical characteristics can improve player performance for better tournament results. It highlights the importance of using these characteristics as guides for improving performance. Effective play increases the chances of winning, while poor performance leads to losing matches.